Delineation of K-3 Cavity Using 2D Imaging Resistivity Technique in Haditha Area (Western Iraq) - Abed , Ali Mishaal; M. Thabit, Jassim (Iraqi Journal of Science, 2023)
The 2D imaging survey was conducted across an unknown K- 3 cavity that is located in Haditha area-Western Iraq.2D measurements are collected along two intercrossing traverses above the cavity with 105m length of each one. Dipole-dipole array is performed with n-factor of 6 and a-spacing equals to 5m. The inverse models of 2D imaging technique showed clearly that the resistivity contrast between the anomalous part of cavity and background resistivity of rocks is about 800:100 Ωm .In addition, the invers models showed that the depth from ground surface to the upper roof of cavity approximately equals to 11m near the cavity operator. So, the K-3 cavity is well defined from 2D imaging with Dipole –dipole array in comparison with the actual depth of this cavity which equals to 11.5m approximatly.It is concluded that the 2D imaging is a useful technique and more effective for determining and mapping subsurface cavities, when the suitable a-electrode spacing and n-factor for the Dipole –dipole array are taken in consideration.